Multifunctional all-in-one drug delivery systems for tumor targeting and sequential release of three different anti-tumor drugs. (January 2016) - Fan, Li; Zhang, Yongsheng; Wang, Fuli; Yang, Qian; Tan, Jiali; Renata, Grifantini; Wu, Hong; Song, Chaojun; Jin, Boquan
Abstract: To achieve active tumor targeting and sequential release of 3 drugs to a tumor site in one nanoparticulate system, self-decomposable SiO2 nanoparticles modified by 3-aminopropyltriethoxysilane (APTS) as their inner structure were used to double load HCPT (in the NP core) and Dox (on the NP surface). Meanwhile, monoclonal antibodies (mAb198.3) against the FAT1 antigen and Bcl-2 siRNA were conjugated onto PEGylated Au-PEG-COOH nanoparticles. The obtained drug-loaded SiO2 nanoparticles were coated with the Au-PEG-mAb.198.3/siRNA nanoparticles through electrostatic interaction to form the SiO2 @AuNP sequential drug delivery system, which featured the controlled and sequential release of siRNA, Dox and HCPT step by step to maximize its anticancer efficacy. The results revealed that the SiO2 @AuNP sequential drug delivery system specifically targeted tumor cells and was internalize rapidly, followed by endosome escape and sequential drug release. Importantly, the sustainable release characteristics of SiO2 made the Tmax difference between HCPT and Dox approximately 8–12 h, and this enhanced the sensitizing efficiency of HCPT on Dox compared with co-administration. The in vivo antitumor results demonstrated that the tumor size after SiO2 @AuNP treatment is 1/400 compared with the saline control group and approximately 1/40 of the HCPT/Dox co-treatment group without any noticeable systemic toxicity.